From Regulation to Realization: A Sociotechnical Study on the Implementation of SIAPKerja in the Work Training Unit of Bali Province - Septiari, Ni Komang Rina; Prabawati, Ni Putu Anik (Universitas Pattimura, 2025)
The advancement of information technology has prompted governments to optimize public services through digital systems, including the implementation of e-Government. This study aims to analyze the implementation of the SIAPkerja (Work Training Administration and Information System) application at the Regional Technical Implementation Unit for Industrial and Tourism Job Training Center (UPTD BLK-IP) in Bali Province, as part of the digital transformation in the employment sector. Using a descriptive qualitative approach over two months, data were collected through direct observation, in-depth interviews with training program administrators, and documentation analysis of technical guidelines and training reports. Findings reveal that successful implementation of SIAPkerja depends on three core elements: government policy support through regulation and system development; resource capacity including funding, IT infrastructure, and human resource competence; and system value in enhancing administrative efficiency and transparency. However, technical challenges persist, such as limited features, delayed report notifications, and inflexible participant data management. This study contributes a sociotechnical perspective by emphasizing the alignment between regulation, technology, and operational practices at the execution level. Key recommendations include continuous field-based evaluation and institutional capacity strengthening to ensure the sustainability of digital transformation in vocational training services. These findings enrich social sciences and humanities discourse on micro-level policy implementation in digital governance.